Sex (2013), volume 6 ebook World hunger. - Casey, Joe (Sex (2013), 2019)
SEX returns in an all-new sixth volume! Return to the world of Saturn City and the various twisted characters who live there, as Simon Cooke embarks on a trek across the world to discover the illicit secrets of the so-called Illuminatileaving his beloved city open to all manner of desperate depravity. You'll never know how much you missed SEX until you read the newest chapter of this continuing saga!. Author: Joe Casey. Illustrator: Piotr Kowalski . 2019 Joe Casey.